Digital radiology to improve the quality of care in countries with limited resources: a feasibility study from Angola. - Floriana Zennaro (Public Library of Science (PLoS), 2013)
Objective Sub-standard quality in X-ray image acquisition and interpretation is common in low-resource countries, and can ultimately result in higher patient morbidity and mortality. This study aimed at evaluating; 1) feasibility of implementing a digital X-ray device in a second level hospital in Angola; 2) quality of digital X-ray images, when digital radiology was in the hands of local technicians; 3) feasibility of digital teleradiology and its potential impact on case management. Methods We developed and tested at the Hospital Divina Providencia (HDP) in Luanda, Angola, a digital X-ray device and a telemedicine network to acquire and print digital X-ray images and send them as DICOM files for remote consultation. Results 20,564 digital X-ray images were made at HDP from November 2010 to December 2012, with no major technical problems and no need for on-site supervision. Digital radiology largely improved the number of X-ray images of good and very good quality (100% of images with digital radiology, compared to 15% of screen-film images, p<0.0001). Teleradiology using digital images was used in 7.6% of paediatric cases, and provided, in these cases, an important contribution to case management. Conclusions The implementation of a digital X-ray device is feasible in low resource settings with significant improvement in quality of X-ray images compared to standard screen film radiology.